THE INVESTIGATION OF STUDENTS’ METACOGNITION IN READING COMPREHENSION - Gita Nurfadhilah (Journal of English and Education, 2016)
The study aims to explore the metacognitive knowledge and regulation of students in senior high school. This study employed a case study design with 33 participants from a public senior high school in Bandung. The data that were obtained through questionnaire and interview. The findings showed that the students are aware of their cognition in reading process. Moreover, they also use all metacognitive regulation strategies in their reading activity although the frequency of metacognitive regulation usage varies. The students use comprehension monitoring the most in their reading activity. The finding also suggests that the least strategy used by the student is information management strategies (18% stated that they never regulate the information they read). The data from this study also show that there are differences of metacognition between high-, medium- and low-achiever students. The frequency of metacognitive regulation is higher in high- and medium- achiever students rather that low-achiever students. The low-achievers tend to focus on strategies when they face failure in comprehension while high- and medium-achievers maintain the use of strategies consistently from the planning stage before reading up to the evaluation stage after reading.